Conjugates between minor groove binders and Zn(II)-tach complexes: Synthesis, characterization, and interaction with plasmid DNA. Issue 21 (25th May 2017) - Sissi, Claudia; Dovigo, Luca; Greco, Maria Laura; Ciancetta, Antonella; Moro, Stefano; Trzciński, Jakub W.; Mancin, Fabrizio; Rossi, Paola; Spalluto, Giampiero; Tecilla, Paolo
Abstract: A new family of conjugates between a Zn(II)-tach complex and (indole)2 or benzofuran-indole amide minor groove binders connected through alkyl or oxyethyl linkers of different lengths has been prepared. The conjugates bind strongly to DNA. However, the complexation to DNA to promote the Zn(II) catalyzed hydrolytic cleavage of the DNA results instead in its inhibition. This inhibition effect has been confirmed also using Cu(II). Modeling studies suggest that in the most stable complex conformation, the minor groove binder and the linker lie in the minor groove hampering the interaction between the metal complex and the phosphate backbone of DNA. Therefore, the linear arrangement of minor groove binder-linker-metal complex appears to be effective to ensure tight binding but unproductive from a hydrolytic point of view. Graphical abstract: